PERANAN KETERANGAN AHLI SEBAGAI ALAT BUKTI DALAM HUKUM ACARA PIDANA - Ahmad Puji Sulistyo Adi; Itok Dwi Kurniawan (Sebelas Maret University, 2023)
This article aims to examine the legality of the pharmacist's testimony in proving that meets the qualifications as evidence according to the Criminal Procedure Code in the case of Supreme Court Decision Number 122/Pid.Sus/2021/PN.Bbs. This article is a prescriptive normative legal research, and uses primary legal materials and secondary legal materials. Data collection techniques using literature studies. The approach used in this article is the case approach. The data analysis technique used is the syllogistic method which uses a deductive mindset. The results of the study show that the legality of the pharmacist's testimony has met the qualifications in Article 179 of the Criminal Procedure Code and the proof of the position of a pharmacy expert witness submitted by the Public Prosecutor is in accordance with Article 184 of the Criminal Procedure Code because members of the National Police provide information for the purposes of investigation, prosecution and justice regarding a criminal case that they heard himself, he saw it himself, and he experienced it himself. Thus, the information given has the same status as an ordinary witness, so that the statement can also be used as material for the judge's consideration in making a decision.Keywords: Strength of Evidence;Expert Information; proof; Unlicensed Drug Circulation